Investigation of the effect of steel fiber (200 mesh size) hybridization on properties of steel/glass fiber and steel/basalt fiber reinforced epoxy composite laminates - Fayzulla, Bayan Jabar; Eroglu, Mehmet; Erklig, Ahmet (Wiley, 2022)
Steel fiber is the most common metal fiber used due to its cost-effectiveness, high performance, and availability despite its heavyweight. This study is an attempt to evaluate the mechanical properties of steel/glass fiber and steel/basalt fiber-reinforced epoxy composites. The symmetric hybrid laminates were produced by replacing the innermost 1, 2, 3, and 4 layers of steel fiber (200 mesh size) with basalt and glass fiber layers. The specimens were subjected to tensile, flexural, and Charpy impact tests in accordance with relevant ASTM standards. Moreover, fracture surfaces were analyzed, and the micrographs were obtained using a scanning electron microscope. The results showed that a high improvement in tensile strength was achieved with BS1-E (1 layer steel mesh-8 layers basalt) and GS(1)-E (1 layer steel mesh-8 layers glass) hybrid composites, with an increase of 528% and 233%, respectively, compared to steel fiber reinforced epoxy composites. Similarly, BS1-E and GS(1)-E hybrid composites showed the highest flexural strength increase of 82.2% and 66.8%, respectively, compared to steel fiber reinforced epoxy composites. Consequently, the potential to hybridize steel fiber with glass fiber and basalt fiber could create new materials with unique physical structures and synergistic effects on mechanical properties.
Keywords: basalt fiber; energy absorption; glass fiber; hybrid composite; mechanical properties; mesh size; steel fiber